Analysis of dephasing time of plasmonic 1 hybridization modes using a quasi-normal mode method - Lun Wang; Boyu Ji; Yang Xu; peng lang; xiaowei song; Jingquan Lin (Optica Publishing Group, 2022)
Near field coupling between different localized surface plasmon (LSP) modes supported by nanoparticles may result in two hybridization modes, namely bonding and antibonding modes. The antibonding mode is similar to the higher-order mode and has a longer dephasing time; the bonding mode has strong locality and higher near-field enhancement. It makes them very attractive in many applications, such as light-emitting electron sources, solar cells, sensors, etc. Measuring and regulating the LSP dephasing time (lifetime) is the basis for the application of LSP devices. Here, we investigated the modulation of the dephasing time of hybridization modes generated by the coupling between a dipole and quadrupole LSP modes in an asymmetric nanorod dimer by combing FDTD numerical simulations with quasi-normal mode (QNM) methods. We surprisingly found that the dephasing time of the antibonding mode can be longer than the one of the quadrupole mode supported by the isolated long rod to more than 30%. Moreover, it is found that the dephasing time of the antibonding and bonding-mode can be selectively modulated by changing the gap size or rod length. We also notice a difference between the peak frequency and the mode resonance frequency for near-field spectra where mode interactions exist. It is proved that QNM has better advantages in analyzing complex spectra and will further advance our understanding of the dynamical evolution of plasmonic hybrid modes.
Keywords: Uncategorized